Exoskeleton-assisted training to enhance lower limb motor recovery in subacute stroke: does timing matter? A pilot randomized trial - Schröder, Jonas; Yperzeele, Laetitia; Embrechts, Elissa; Loureiro-Chaves, Renata; Hallemans, Ann; Lafosse, Christophe; Truijen, Steven; Kwakkel, Gert; Saeys, Wim (Frontiers in Stroke, 2024)
Background: Lower limb motor recovery, including abnormal muscle synergies, occurs mainly within the first 5-8 weeks after a stroke. This suggests the importance of delivering impairment-focused therapies, such as therapeutic robots that promote symmetric gait, during this time-sensitive period, following the principle of “the earlier, the better”. Objective: First, to compare early robotic training (ERT) with usual care (UC) against UC alone on restoring intralimb muscle synergies and interlimb symmetry during functional tasks; Second, to investigate whether ERT is superior to delayed robotic training (DRT) starting after the proposed time-sensitive period. Methods: This observer-blinded, randomized pilot trial with crossover design involved 19 nonambulatory adults included within 14 days poststroke. Those allocated to ERT (N=10) received immediately 4 weeks of training (16 sessions, 4x/week) with the Ekso GT® above UC and were compared with the DRT group (N=9) who received UC alone at this point. Thereafter a 3-week UC period followed to investigate sustainability of ERT and the interventional roles were exchanged; at about week 8 poststroke DRT subjects started the same experimental robotic protocol and ERT subjects continued UC as controls. Outcomes included changes in Fugl-Meyer lower extremity scores (FM-LE) reflecting muscle synergies, weight-bearing asymmetry (WBA), and dynamic control asymmetry (DCA) during quiet standing. Functional ambulation category (FAC) was used to classify walking independence (cut-off ≥ 4). Results: A trend toward earlier reacquisition of walking independence favoring ERT with UC over UC was not accompanied by differences in FM-LE, WBA, or DCA (first objective). Thereafter, DRT with UC did not yield any significant changes relative to UC, such that no between-group differences were found favoring restorative effects of ERT over DRT (second objective). Conclusion: This pilot trial shows the feasibility of investigating a wearable exoskeleton as an adjunct therapy in subacute stroke. Nevertheless, our preliminary findings suggest that motor recovery of lower limb muscle synergies was not enhanced by 4 weeks of robotic training to reduce compensations with the less-affected side, irrespective of the timing of application. Trial registration: ClinicalTrials.gov identified: NCT03727919